POLA GURU BIMBINGAN DAN KONSELING DALAM PENANGANAN SISWA BERMASALAH DI SMA PGRI 4 PALEMBANG - Muhammad Ferdiansyah; Efrianto Efrianto (Program Studi Bimbingan dan Konseling Universitas Muhammadiyah Tasikmalaya, 2018)
The purpose of this research is to find out and evaluate the form of handling pattern of troubled students conducted by guidance and counseling teacher at pgri 4 senior high school palembang. the research method used in this research is qualitative method with descriptive explanatory level. data collected through interviews, observation and documentation. further data analyzed refers to miles and huberman analysis model with data reduction, data presentation and conclusion. the results showed that the pattern of handling palembang was dominated by disciplinary approach with the imposition of sanctions which is conducted by guidance and counseling teacher in pgri 4 senior high school palembang.